Heuristic potentiality and applicability limits of the anthropic principle - Savlukova, Elizaveta V.; Barsuk, Irina A. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The article examines the anthropic principle in modern scientific knowledge, demonstrates its interpretations, shows its heuristic potential, and substantiates the limits of applicability in post-non-classical science. It is revealed that the philosophical, ideological and methodological foundations of the anthropic principle acquire the status of a universal construct in the formation of the modern scientific picture of the world. It is substantiated why the anthropic principle allows theoretically solving a number of fundamental issues of modern astrophysics and cosmology. The interrelation of the concept of global evolutionism with socio-humanitarian and natural science cognition is presented representatively.